KosherSoul : the faith and food journey of an African American Jew - Twitty, Michael, 1977- (Amistad, an imprint of HarperCollinsPublishers, 2022)
"The James Beard award-winning author of the acclaimed The Cooking Gene explores the cultural crossroads of Jewish and African diaspora cuisine and issues of memory, identity, and food. In Koshersoul, Michael W. Twitty considers the marriage of two of the most distinctive culinary cultures in the world today: the foods and traditions of the African Atlantic and the global Jewish diaspora. To Twitty, the creation of African-Jewish cooking is a conversation of migrations and a dialogue of diasporas offering a rich background for inventive recipes and the people who create them. The question that most intrigues him is not just who makes the food, but how the food makes the people. Jews of Color are not outliers, Twitty contends, but significant and meaningful cultural creators in both Black and Jewish civilizations. Koshersoul also explores how food has shaped the journeys of numerous cooks, including Twitty's own passage to and within Judaism. As intimate, thought-provoking, and profound as The Cooking Gene, this remarkable book teases the senses as it offers sustenance for the soul. Koshersoul includes 48-50 recipes"--